Qu’est-ce qui s’apprend dans les premiers moments du travail et comment ? - Claire Tourmen; Annie Leroux; Sylvie Beney (Perspectives Interdisciplinaires sur le Travail et la Santé)
Professional learning is often considered as a long process requiring repeated and varied experiences. That being said, the question of the duration of learning remains. We wished to explore what is learnt during the first moments of work, what is the role of observation, and whether this initial professional learning has a cultural dimension. We used a theoretical framework from vocational didactics, inspired by research in the psychology of work and ergonomics studies, to perform a task analysis of social work in two organizations. We then analyzed the activity of six experienced workers and three interns in their first year of study in social work. Results showed that learning occurred as soon as work began and that the very first learning dealt with what could be called the “cultural” dimensions of work environments. We propose using the concept of “scene” (Valsiner, 2007) to analyze initial professional learning.